The relationship between the income and behavioural biases - Isidore R., Renu (2019)
Purpose - The purpose of this paper is to test the relationship between the annual income earned by the investors and eight behavioural biases exhibited by the investors such as mental accounting, anchoring, gambler’s fallacy, availability, loss aversion, regret aversion, representativeness and overconfidence. Design/methodology/approach - The relationship is derived based on a questionnaire survey conducted on 436 secondary equity investors residing in Chennai, India. Findings - Analysis of variance test was performed on the normalised and non-normalised version of the biases divided in terms of the annual income earned by the investor. The test found that for the significant biases except the overconfidence bias, the investors with higher annual income were less prone to the biases when compared to investors with lower annual income. On the other hand, with respect to the overconfidence bias, the investors with higher annual income were prone to exhibit overconfidence bias when compared to the investors with lower annual income. Correlation analysis showed that the investors with high annual income were more likely to exhibit higher overconfidence bias but lower representativeness, loss aversion, availability and mental accounting biases. Originality/value - A contribution in the financial and economic front which would benefit the financial advisors to now consider the income earned by the clients as an important factor while giving financial advice to the clients and while guiding them about the biases they are prone to exhibit.